Adoption a payment fintech service by food and beverage MSMEs: Evidence from east java Indonesia - Maghfiroh, Rahma Ulfa; Djatmika, Ery Tri; Handayati, Puji; Wardoyo, Cipto (Edelweiss Applied Science and Technology, 2025)
This study uses the Technology Acceptance Model (TAM) approach to identify the characteristics influencing MSMEs’ desire to use fintech for payments. The participants in this study were Indonesian MSMEs adopting digital payments among MSMEs in Surabaya’s food and beverage industry. This study employs a quantitative survey approach to determine the factors that drive the adoption of digital payments by micro food and beverage entrepreneurs. The user attitude variable (attitude toward using) is chosen as a mediating variable, while the variables perceived ease of use and perceived usefulness are independent. The micro businesses studied are micro food and beverage enterprises spread across culinary centers in 31 sub-districts in Surabaya City, with a population of digital payment users in culinary centers of 472 MSMEs. The structural equation model (SEM) was chosen as the analysis technique for this study. The study’s results indicate that the factors perceived usefulness affect user attitude and adoption of fintech payments. At the same time, perceived ease of use does not affect the attitude toward using or adopting fintech payments. The variable attitude toward using can mediate perceived ease of use on fintech payments.